Assessing the Productivity of Information Technology Equipment in U.S. Manufacturing Industries - Morrison, Catherine J. (The Review of Economics and Statistics, 1997)
We assess the cost-reducing impacts of increasing stocks of “high-tech” equipment (O capital). Our empirical analysis is based on a dynamic production theory model and annual data for two-digit U.S. manufacturing industries (1952–1991). We find evidence of overinvestment in O capital in the mid to late 1980s, following a period of strong investment incentives in the late 1970s. By the end of the 1980s, however, the returns to investment and falling prices for O capital more than justified the high investment levels in nondurable-goods industries, and the benefit–cost ratio was also increasing for durable-goods industries. The underlying substitution patterns suggest that high-tech capital expansion increases demand for most capital and noncapital inputs overall, but saves on materials inputs. In durables industries, however, both energy and “other” capital appear somewhat substitutable with O capital, and in nondurables industries increasing high-tech intensity may be a factor underlying stagnating labor demand.“We see computers everywhere except in the productivity statistics.”Attributed to Robert M. Solow